Comparison of adenoma detection rate between three-dimensional and standard colonoscopy: a multicenter randomized controlled trial - Chang, Wei-Yuan; Liao, Wei-Chih; Chang, Li-Chun; Lin, Hsuan-Ho; Wei, Pin-Ya; Wu, Hsing-Chien; Chiu, Han-Mo; Wu, Ming-Shiang (Endoscopy, 2025)
Improvement in adenoma detection rates (ADRs) effectively reduces the incidence of colorectal cancer. In a simulation study, three-dimensional (3D) colonoscopy provided more anatomical details than standard two-dimensional (2D) colonoscopy and improved ADR. We compared ADRs between 2D and 3D colonoscopy.In this multicenter randomized controlled trial, participants aged ≥40 years undergoing colonoscopy for screening, surveillance, or symptoms between February 2022 and June 2023 were randomized 1:1 into 2D or 3D groups. The primary outcome was ADR. Secondary outcomes included detection rates for flat adenomas, right-sided adenomas, proximal adenomas, advanced adenomas, and sessile serrated lesions (SSLs).Of 348 participants recruited, data from 158 (2D group) and 160 (3D group) were analyzed. Mucosa inspection time was comparable between the 3D (9.8 [SD 2.6] minutes) and 2D (9.4 [SD 3.1] minutes) groups (P = 0.21). Compared with the 2D group, the 3D group had a significantly higher ADR (53.1% vs. 38.6%; difference 14.5% [95%CI 3.7 to 25.4]; P = 0.009), and higher detection rates for flat adenomas (35.0% vs. 21.5%; difference 13.5% [95%CI 3.7 to 23.3]; P = 0.008), right-sided adenomas (26.3% vs. 15.2%; difference 11.1% [95%CI 2.2 to 19.9]; P = 0.02), proximal adenomas (38.1% vs. 23.4%; difference 14.7% [95%CI 4.7 to 24.7]; P = 0.005), and adenomas sized 5–9 mm (45.0% vs. 31.0%; difference 14.0% [95%CI 3.4 to 24.5]; P = 0.01). There was no difference in detection rates for SSLs or advanced adenomas.3D colonoscopy improved adenoma detection without significantly increasing the mucosa inspection time.